How Close Are Western Cham Language and Bahasa Indonesia in their Structure? A Contrastive Study - Math Safeat; Muhammad Hafiz Kurniawan (Universitas Ahmad Dahlan, 2019)
Western Cham spoken in Cambodia is categorized as Malay-Polynesian under the West Malay Polynesian with the largest speakers compared to its sister, Eastern Cham spoken in Vietnam. The fallen kingdom of Champa in 1442 brought pervasive and massive change to this language both spoken and writing system. The language contact between these languages to the neighboring language makes these languages survive by adopting the phonotactics of neighboring languages. However, this change can be traced back to its family and this research aims to find and to describe the difference and similarity between Bahasa Indonesia and Cham language using contrastive analysis. This analysis is used to elaborate the phrase structure, and simple clause structure with different voices, negation, and the use of adverb already which has its unique application. This research, which was fully funded by PPSDK (Pusat Pengembangan Stategi Diplomasi dan Kebahasaan) under the Ministry of Education of Republic Indonesia and also supported by Universitas Ahmad Dahlan and Musa Asiah Foundation (YASMA), was conducted in four months in a Muslim private School in Krouch Chmar, Cambodia and has secondary aim to support the development of this language and to preserve it from language endangerment status, because of its limited use in social settings.